2002
DOI: 10.1002/cne.10378
|View full text |Cite
|
Sign up to set email alerts
|

Chemoarchitecture of GABAergic neurons in the ferret superior colliculus

Abstract: gamma-Aminobutyric acid (GABA)ergic neurons are thought to play a key role both in visual processing and in the complex sensory-motor transformations that take place in the mammalian superior colliculus. To understand the organization of GABAergic neurons in the ferret superior colliculus, we applied antisera to several markers of GABAergic function, including GABA, two isoforms of its synthetic enzyme glutamic acid decarboxylase (GAD-65 and GAD-67), and the GABA transporter, GAT-1. We also applied antisera to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 109 publications
(166 reference statements)
8
28
1
Order By: Relevance
“…Presenting two stimuli in succession, within single RFs of superficial layer SC neurons, results in a suppressed response compared with when one stimulus is presented alone (Rizzolatti et al, 1973(Rizzolatti et al, , 1974Wurtz et al, 1980). Anatomical evidence reveals GABA neurons distributed uniformly throughout the SC (Mize, 1992;Behan et al, 2002). The present results demonstrate short-range competitive interactions influencing SC neurons.…”
Section: Stimulus Interactions and Saccade Selectionsupporting
confidence: 44%
“…Presenting two stimuli in succession, within single RFs of superficial layer SC neurons, results in a suppressed response compared with when one stimulus is presented alone (Rizzolatti et al, 1973(Rizzolatti et al, , 1974Wurtz et al, 1980). Anatomical evidence reveals GABA neurons distributed uniformly throughout the SC (Mize, 1992;Behan et al, 2002). The present results demonstrate short-range competitive interactions influencing SC neurons.…”
Section: Stimulus Interactions and Saccade Selectionsupporting
confidence: 44%
“…The pattern of CR-immunostaining in the SC described in the present study was in agreement with that reported previously (Behan et al, 2002). In the superficial layers, CR-immunostaining consisted of heavily immunostained fibers and terminals as well as a few immunostained somata that were, in the majority of the cases, lightly immunostained ( Fig.…”
Section: Control Animalssupporting
confidence: 93%
“…Since electrical activity in the SC is regulated by GABA (Chevalier et al, 1985; Chevalier and Deniau, 1990; Hall and Lee, 1993; Lee et al, 2001, 2007; Behan et al, 2002; Kaneda et al, 2008; Isa and Hall, 2009), we tested the actions of two GABA A receptor antagonists, bicuculline (50 μ m) and gabazine (SR95531, 5 μ m) (bicuculline and gabazine were used interchangeably and the results combined). These drugs generally increased the amplitude of optical signals, but had the greatest effects on after-depolarizations (Fig.…”
Section: Resultsmentioning
confidence: 99%